Research of the reasons for people’s willingness to take overtaking behavior in emergency evacuation based on the theory of extended planned behavior - Jiandong Cheng; Yuanchun Ding; Zirui Nie (Scientific Reports)
Abstract Using the extended theory of planned behavior, this study investigates the factors influencing individuals’ willingness to engage in overtaking behavior during emergency evacuations and explores the causal relationships among these factors. The proposed model includes 7 direct effect hypotheses, 6 mediation effect hypotheses, and 4 multiple mediation effect hypotheses. Empirical analysis revealed that 10 hypotheses were validated. Key findings indicate that disaster awareness, behavioral attitude, perceived behavioral control, and the evacuation environment directly influence overtaking behavior during emergency evacuations. Behavioral attitude, subjective norms, and perceived behavioral control mediate the relationship between disaster awareness and the willingness to adopt overtaking behavior. Additionally, the evacuation environment influences overtaking behavior through the partial mediation of subjective norms. Subjective norms and behavioral attitudes also play multiple mediating roles between disaster awareness and evacuation behavior.